2008
DOI: 10.1242/dev.008490
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of antisense transcription across theXistpromoter inTsix-mediatedXistchromatin modification

Abstract: Expression of Xist, which triggers X inactivation, is negatively regulated in cis by an antisense gene, Tsix, transcribed along the entire Xist gene. We recently demonstrated that Tsix silences Xist through modification of the chromatin structure in the Xist promoter region. This finding prompted us to investigate the role of antisense transcription across the Xist promoter in Tsixmediated silencing. Here, we prematurely terminated Tsix transcription before the Xist promoter and addressed its effect on Xist si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 29 publications
(43 reference statements)
4
105
1
4
Order By: Relevance
“…Extensive studies on Tsix in mouse embryos and ES cells with genetic manipulations have demonstrated that Tsix is a negative regulator of Xist and its expression prevents the upregulation of Xist on the same X chromosome by facilitating the formation of a repressive chromatin configuration at the Xist promoter (Lee & Lu 1999, Lee 2000, Sado et al 2001, Navarro et al 2005. Although it is not clear which of the RNA products or the action of antisense transcription is critical for its function, transcription across the Xist promoter appears to be crucial for Tsix to exert its negative effects on Xist (Ohhata et al 2008). At the onset of X-inactivation, the downregulation of Tsix on one X allows the differential upregulation of Xist in cis and induces subsequent inactivation of the X, whereas continued expression of Tsix on the other X prevents the upregulation of Xist and keeps the X active.…”
Section: X-linked Lncrnas That Coat An X Chromosomementioning
confidence: 99%
“…Extensive studies on Tsix in mouse embryos and ES cells with genetic manipulations have demonstrated that Tsix is a negative regulator of Xist and its expression prevents the upregulation of Xist on the same X chromosome by facilitating the formation of a repressive chromatin configuration at the Xist promoter (Lee & Lu 1999, Lee 2000, Sado et al 2001, Navarro et al 2005. Although it is not clear which of the RNA products or the action of antisense transcription is critical for its function, transcription across the Xist promoter appears to be crucial for Tsix to exert its negative effects on Xist (Ohhata et al 2008). At the onset of X-inactivation, the downregulation of Tsix on one X allows the differential upregulation of Xist in cis and induces subsequent inactivation of the X, whereas continued expression of Tsix on the other X prevents the upregulation of Xist and keeps the X active.…”
Section: X-linked Lncrnas That Coat An X Chromosomementioning
confidence: 99%
“…We previously showed that transcription overlapping the Xist promoter region is necessary for Tsix function (Ohhata et al 2008). Furthermore, several studies have shown that the endogenous Tsix promoter can be substituted for a constitutive or a tetracycline-responsive (Tet) promoter (Luikenhuis et al 2001;Stavropoulos et al 2001).…”
mentioning
confidence: 99%
“…Furthermore, several studies have shown that the endogenous Tsix promoter can be substituted for a constitutive or a tetracycline-responsive (Tet) promoter (Luikenhuis et al 2001;Stavropoulos et al 2001). Recruitment of DNA methylation and histone modifications such as H3K27me3 around the Xist promoter by Tsix have been reported in differentiated ES cells (Navarro et al 2006;Nesterova et al 2008), embryos (Sado et al 2005), and visceral endoderm (Ohhata et al 2008). Interactions of Tsix RNA with the DNA methyltransferase Dnmt3a (Sun et al 2006) and the PRC2 protein Ezh2 (Zhao et al 2008) have been reported with implications for the mechanism of Tsix-mediated recruitment of these modifications on the Xist promoter.…”
mentioning
confidence: 99%
“…Xist INV was generated from Xist Ex4del by a targeted inversion disrupting conserved sequences beginning 6 kb into exon 1 and extending to intron 5. Xist IVS was originally generated for the study of Tsix-mediated antisense regulation of Xist by Ohhata et al [41]. It contains an exogenously introduced 1 kb intron at 0.9 kb from the major transcription start site.…”
Section: Functional Domains Of Xist Rnamentioning
confidence: 99%